2020
DOI: 10.51239/nrjss.v13i3.191
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance, Bank Performance and Value:-Evidence from Pakistan

Abstract: The study aims to examine the relationship of board structure, ownership structure, and bank-specific variables with bank performance and value. Panel Data is collected from eighteen conventional commercial banks of Pakistan for the time period of 2012 to 2017. The analysis is carried out by employing pooled OLS model estimation, descriptive statistics, and correlation analysis, using Eviews-9, with 108 observations. The board size and board independence are found to have a determinant effect on the bank perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…All the control variables such as asset quality, liquidity, capitalization and bank size showed mixed results with different measures of bank performance (Menicucci and Paolucci, 2016;Farag et al, 2017;Ghosh, 2017;Jayati and Subrata, 2018;Ali et al, 2020). company through effective ACs.…”
Section: Tablementioning
confidence: 95%
See 3 more Smart Citations
“…All the control variables such as asset quality, liquidity, capitalization and bank size showed mixed results with different measures of bank performance (Menicucci and Paolucci, 2016;Farag et al, 2017;Ghosh, 2017;Jayati and Subrata, 2018;Ali et al, 2020). company through effective ACs.…”
Section: Tablementioning
confidence: 95%
“…By gathering the data of 18 commercial banks from 2012 to 2017, the study of Ali et al (2020) observed that larger board significantly improves the accounting and market measures of bank performance. Several other studies have also reported the similar effect (Arora and Sharma, 2016; Farag et al , 2017; Gordini and Rancati, 2017; Herdjiono and Sari, 2017; Adeabah et al , 2018; Andersson and Wallgren, 2018; Riyadh et al , 2019; Aslam and Haron, 2021).…”
Section: Theoretical Foundation Literature Review and Hypothesis Deve...mentioning
confidence: 99%
See 2 more Smart Citations